"First in Man": Case Report of Selective C-Reactive Protein Apheresis in a Patient with Acute ST Segment Elevation Myocardial Infarction. (6th November 2018) - Ries, Wolfgang; Sheriff, Ahmed; Heigl, Franz; Zimmermann, Oliver; Garlichs, Christoph D.; Torzewski, Jan
Abstract : C-reactive protein (CRP) may be causative in cardiovascular disease. As yet, no specific CRP inhibitor for human application has been described. A 69-year-old male was referred with ST segment elevation myocardial infarction (STEMI). Typical symptoms of chest pain started at 10.00 p.m. The patient was admitted to the hospital at 1.30 a.m. the next day. As ECG showed anterior wall myocardial infarction, the patient was immediately transferred to successful emergency angioplasty/drug-eluting- (DE-) stenting of the subtotally occluded left anterior descending artery. Consecutively, the hemodynamically stable patient was monitored at the chest pain unit. C-reactive protein (CRP) apheresis using the CRP adsorber (PentraSorb® CRP) within CAMI-1 trial was performed 34 h and 58 h after the onset of symptoms. In each apheresis session, 6000 ml plasma was treated via peripheral venous access. Plasma CRP levels decreased from 28.77 mg/l to 12.58 mg/l during the first apheresis session and from 24.17 mg/l to 11.55 mg/l during the second session, respectively. No side effects were observed. This is the first report of selective CRP apheresis in a man. The technology offers multiple opportunities to clarify the immunological/pathogenic role of CRP in health and disease.